HISTORICAL-DEMOGRAPHIC DETERMINANTS FOR TRNAVA MUNICIPALITY FROM 1839 TO 1945 (Heritage, 2025)
Stara Raška was the medieval capital of Serbia and an area that became an important center of Serbian Nemanjić rulers, Serbian culture and spirituality. On the eastern slopes of the Golija mountain, at a distance of 9 km from the town of Raška, there is the village of Trnava. In the period from 1839 to 1945, this rural settlement went through significant political and historical-demographic imbalances. Frequent changes in state structures: the Principality of Serbia, the Kingdom of Serbia, the Kingdoms of Serbs, Croats and Slovenes, then the Kingdom of Yugoslavia influenced the formation of a specific administration and judiciary, the center of which was the village of Trnava. The municipal area consisted of six villages: Boroviće, Milatoviće, Nosoljin, Plešin, Sebimilje and Trnava. The Balkan wars, the First World War and the Second World War caused complex historical-demographic changes. With the creation of the Kingdom of Serbs, Croats and Slovenes (1918), the municipality of Trnava became an area burdened by the consequences of the war, which were felt in the living conditions of the population. In the period between the Balkan Wars and the First World War, the total number of inhabitants was reduced by 15.93%. In addition to wars, the high mortality of the population was also affected by epidemics of infectious diseases. The goal of the historical-demographic studies of the municipality of Trnava is to study and analyze the administrative and territorial changes and the dynamics of the population development of the municipality of Trnava based on previous research and collected archival material. The research was carried out using the historical-demographic and demographic-statistical method using previous research and based on archival sources from the Historical Archive in Kraljevo, which have not been published so far. The importance of historical-demographic research of the municipality of Trnava in the time frame of 106 years (1839-1945) tends to contribute to new knowledge about the Raška region and rural settlements: Boroviće, Milatoviće, Nosoljin, Plešin, Sebimilje and Trnava. The resulting research will help in understanding and explaining the complex administrative-territorial and demographic changes in the central part of the Raška region from 1839 to 1945. This type of research should improve existing knowledge and develop new concepts research in the function of contributing to the growth and development of science in the field of historical-demographic research.
Keywords: Historical-demographics, Raška, Trnava, Studenički srez